The Relationship Between Perineal Body Size, Total Vaginal Length, Apical Prolapse, and Prolapse Symptoms. Issue 9 (24th September 2022) - Kinay, Tugba; Tapisiz, Omer Lutfi; Kiykac Altinbas, Sadiman; Kayikcioglu, Fulya; Karakaya, Jale; Moraloglu Tekin, Ozlem
Abstract : Importance: Currently, apical prolapse is diagnosed via assessing the levels of C and D points in the pelvic organ prolapse quantification (POP-Q) system. However, it is not yet known whether the other components of this system are useful for diagnosing apical prolapse and its symptoms. Objective: The aim of the study was to evaluate the association between the perineal body size (PB), total vaginal length (TVL), and apical prolapse and its symptoms. Study Design: Two hundred women, 100 women with apical prolapse and 100 women without, were included in this cross-sectional study. The association between the PB, TVL, and apical prolapse and its symptoms were evaluated. The relationship between the other POP-Q measurements and apical prolapse/prolapse symptoms were also evaluated as the secondary outcome of the study. Results: The TVL (cutoff value, ≤8 cm; sensitivity, 80%; specificity, 60%) and the genital hiatus size (GH; cutoff value of >4.5 cm; sensitivity, 90%; specificity, 91%) were significantly associated with apical prolapse. The PB cutoff value of 3.4 cm or less had lower sensitivity (49%) and specificity (70%) for the diagnosis of apical prolapse. The GH (cutoff value, >4.8 cm; area under curve [AUC], 0.927), C (cutoff value, >−5.8 cm; AUC, 0.955), and Ba (cutoff value, >−1.1 cm; AUC, 0.891) were significantly associated with apical prolapse symptoms. However, there was no association between the PB or TVL with symptoms. Conclusions: The study results showed that the TVL and GH were more strongly associated with apical prolapse than PB. The GH, C, and Ba were also associated with prolapse symptoms, but PB and TVL were not.